Sleep and Quality of Life in Clinical Medicine - Verster, Joris C. (Springer, 2017)
The first of its kind, Sleep and Quality of Life in Clinical Medicine provides an evidence-based introduction to the interface between sleep wide range of medical disorders. Many patients experience sleep disturbances secondary to their primary illness and this often has a negative effect on their quality of life. Sleep and Quality of Life in Clinical Medicine is essential reading for all health care professionals concerned with their patients’ well being. A clinically focused, comprehensive review for physicians and other health providers, this volume is a state-of-the-art reference work that can also serve as a textbook for students and researchers who wish to become familiar with the impact of sleep on quality of life.